The relationship between retirement planning behavior and risk tolerance among urban adult employees in Malaysia - Goh, Zi Wei; Lee, Hao Xian; Lee, Jun Han; Tan, Jing Yang (2023)
This research paper aimed to determine the relationship between retirement planning behavior and risk tolerance among urban area employees in Malaysia. In this study, there are three independent variables, including risk tolerance, financial knowledge, and propensity to plan. The theory applied in this study are principle of propensity to plan, risk-bearing and consumption theory, and theory of planned behavior. The target population in our research are those Malaysian who in working age between 15-64 years old, including early working ages, middle working age and old-working age employees in urban area Malaysia. Smart PLS software has been applied in this study for compute, measure, and determined the statistical results in our research. The major findings show that financial knowledge is not correlated to the retirement planning behavior, but risk tolerance and propensity to plan are both correlated. At the same time, gender as a moderator has no moderating effect in the interaction between propensity to plan and retirement planning behavior, while it has not moderated effect in the interaction between risk tolerance and retirement planning behavior, as well as the interaction between financial knowledge and retirement planning behavior.